IMPROVING WRITING ACHIEVEMENT ON DESCRIPTIVE TEXT AT THE EIGHT GRADE STUDENTS OF SMP WAHID HASYIM MALANG USING MIND MAPPING - Dipta Laksmi Prianka (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
ABSTRACT: This study used to Classroom Action Research (CAR). It is aimed to find out the Improving Writing Achievement on Descriptive Text at the Eight Grade Students of SMP Wahid Hasyim Malang. Students get some difficulties on how to write in English. When the students write descriptive text, they should have imagination to gain idea, a skill of writing, and should also master some vocabularies. The students could not describe animal in detail because they do not have any ideas when they are asked to describe that.Many studies indicate that teacher did not teach the students of how to write English but only give task to them. Meanwhile, the students wrote the text without guidance from the teacher. In SMP Wahid Hasyim Malang, especially students in the eighth grade, there was problem in writing. Only 10 students or 28% passed the minimum score or KKM which is 75. It means that there were 26 students or 72% who got problems. The researcher then proposed to use mind mapping as teaching strategy to improve students’ skill in writing a descriptive text.The subject of this study was 36 students in eight grade of SMP Wahid Hasyim Malang. The researcher planned cycle 1 to conduct the research by following some procedures:  planning, action, observation, and reflection. These procedures were did starting from preparing the lesson plan and the criteria of success until reflection the result of cycle 1. If the result of the research reaches the target improvement or criteria of success which was stated that minimally 70% students must reach the KKM, the research will be stopped. If not, it must be continued by revising the cycle.The findings of the research showed that the use mind mapping technique could improve the writing skills of eight grade students. It was proven that by results of mean score of writing test which has increased from 66 to 81 and the students passed the KKM were 31 students or 86%. Only 5 students or 14% failed the KKM. It means that there was high improvement for 57%. Based on that finding, the cycle 1 was stopped because it reached the criteria of success. As the conclusion, mind mapping can improve the students writing skill if it is implemented well. So, the teacher who gets the same problem in their class can use mind mapping as the solution. For further researchers, they can do research with mind mapping in the different case and situation. Keywords: mind mapping, writing, classroom action research